2013
DOI: 10.1148/radiology.13122617
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Chest and Abdominopelvic CT: Organ Dose Estimation Based on 42 Patient Models

Abstract: Purpose:To estimate organ dose from pediatric chest and abdominopelvic computed tomography (CT) examinations and evaluate the dependency of organ dose coefficients on patient size and CT scanner models. Materials and Methods:The institutional review board approved this HIPAA-compliant study and did not require informed patient consent. A validated Monte Carlo program was used to perform simulations in 42 pediatric patient models (age range, 0-16 years; weight range, 2-80 kg; 24 boys, 18 girls).Multidetector CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The dependence of organ dose on patient size has been extensively studied using validated Monte Carlo simulation. A number of groups reported that CTDIvol normalized organ dose as a function of patient size can be approximated as an exponential curve (11,24). Their findings can be combined with our findings here to develop a complete methodology for accurate and robust determination of breast dose from CT studies.…”
Section: Discussionsupporting
confidence: 60%
“…The dependence of organ dose on patient size has been extensively studied using validated Monte Carlo simulation. A number of groups reported that CTDIvol normalized organ dose as a function of patient size can be approximated as an exponential curve (11,24). Their findings can be combined with our findings here to develop a complete methodology for accurate and robust determination of breast dose from CT studies.…”
Section: Discussionsupporting
confidence: 60%
“…This has been performed using a benchmarked Monte Carlo radiation transport program across the population of human models for a variety of CT systems [8,16,17]. With a fixed irradiation condition over the scanned field of view, organ doses are estimated by tallying the energy deposited in each organ.…”
Section: Modeling Irradiation Conditionmentioning
confidence: 99%